Not in the Shopping Cart - On the experiential aspects of retail shopping centers - Hanna Larsson; Erik Åsberg (European Regional Science Association (ERSA), 2010)
Not in the Shopping Cart -On the experiential aspects of retail shopping centers It is not hard to imagine that consumers value not only what they have bought in a store and can take home with them, but also the experience that was entailed in the actual purchase. The aim of the study is to investigate and explain what experiential factors influence Swedish shopping center consumers. Based on previous shopping centre sales estimations we conduct an analysis based on the residual from this and regress a number of independent variables measuring different aspects of experiences on it. Experience enhancing features are defined to include, but not be limited to, cinemas, bowling alleys, libraries and museums. Preliminary estimations, and anecdotal evidence, indicate that the experiential aspect of shopping plays a limited role in explaining the behavior of Swedish consumers and that this differs somewhat from previous estimations from other countries. Common areas in a shopping center, which can plausibly be thought to enhance the shopping experience and provide an arena for activities such as musical performances is however found to have a significant impact on revenue above what is predicted by the original model. Hanna Larsson , PhD Candidate, Hanna.Larsson@ihh.hj.se Erik Åsberg , PhD Candidate, Erik.Asberg@ihh.hj.se Jönköping International Business School
Keywords: C21; D12; L81; O18; R10; 330